PENGENDALIAN HAMA KUMBANG BADAK YANG MENYERANG KELAPA DI DESA LOJEJER KECAMATAN WULUHAN KABUPATEN JEMBER - Tri Haryadi, Nanang; Giyarto (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2024)
Lojejer Village has significant coconut resources, making it a center for the coconut sugar industry in Jember Regency. Currently, the production of sap from coconut trees in Lojejer Village is declining daily due to attacks by rhinoceros beetle pests (Oryctes rhinoceros). O. rhinoceros infestation damages the growth points of coconut trees, leading to tree death. This pest thrives in Lojejer Village because of the abundance of animal manure near the coconut trees, providing an ideal environment for egg-laying. If left unchecked, O. rhinoceros attacks will threaten the coconut sugar industry, a primary source of livelihood for the community. The proposed solution to address this issue is an integrated control of O. rhinoceros by using sex pheromones, the entomopathogenic fungus Metarhizium anisopliae, and manually removing O. rhinoceros larvae from manure piles. The results of the control efforts in Lojejer Village will be published as a scientific article in a community service journal, aiming to reduce the rhinoceros beetle population and the intensity of attacks.